Evaluation of the anti-inflammatory/chondroprotective activity of aldose reductase inhibitors in human chondrocyte cultures. Issue 5 (13th May 2015) - Panico, Annamaria; Maccari, Rosanna; Cardile, Venera; Avondo, Sergio; Crascì, Lucia; Ottanà, Rosaria
<x xml:space="preserve">Abstract</x> 2-Thioxo-4-thiazolidinone derivatives active as aldose reductase inhibitors were able to control key inflammatory/degenerative events induced by IL-1β in human chondrocytes, appearing to be promising candidates in the search for novel anti-inflammatory agents.